Kegunaan Dan Manfaat Manajemen Pendidikan Islam Dalam Pengembangan Ilmu Pengetahuan: Paradigma Manajemen Pendidikan Islam sebagai Epistemologi Pengembangan Ilmu Pengetahuan - Neneng Kurnia; Ahmad Zain Sarnoto (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Islamic education management has a strategic role in the development of science by placing management as an epistemological paradigm. Management shapes the direction, method, and orientation of scientific development through policies, institutional structures, and managed academic culture. Literature reviews are conducted on books, scientific journals, academic articles, as well as policies and guidelines for the management of relevant Islamic educational institutions. The results of the study show that the management of Islamic education does not only function administratively, but also builds a managed scientific rationality, supports the production of knowledge in a systematic, directed, and responsible manner, and maintains academic integrity. Management also allows the integration of modern science and Islamic scientific traditions dialogically, so that the development of knowledge is reflective, critical, and adaptive. Thus, the management of Islamic education contributes to the birth of an integrative, value-oriented, rational, and transcendental scientific paradigm, and supports the creation of the development of science that is meaningful, sustainable, and plays a role in the advancement of scientific civilization.